Utilization of alternative and augmentative communication resources by patients with amyotrophic lateral sclerosis. - Moraes, Micaele Kedma Ribeiro de; Santos, Vagner Rogério dos; Fávero, Francis Meire; Oliveira, Acary Souza Bulle; Rosseto, Lucimar Pinheiro; Tacon, Kelly Cristina Borges; Fernandes, Viviane Lemos Silva; Parreira, Samara Lamounier Santana (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is a multisystemic impairment disease, among them, the total loss of communicative abilities. Augmentative and Alternative Communication (CAA) seeks to provide effective communication through specific resources. Objective: To verify the influence of ALS on aspects of personal, social and environmental life in patients who use the CAA. Methods: This is a qualitative, exploratory, longitudinal research of a series of cases. The patients with ALS were invited to participate of an evaluation with a sociodemographic and semi-structured questionnaire. Each participant obtained a CAA resource offered by the present research and returned for a reevaluation. Results: The analysis based on the reports that emerged from the spontaneous comments and generated five categories (socialization, social attitudes, communication and rights, services, systems and policies, and family interaction). Conclusion: Even with the use of CAA, ELA generates negative impacts on socialization and social participation due to social and environmental factors.